Calorímetro de gelo : uma abordagem histórica e experimental para o ensino de química na graduação - Tavares, Guilherme W. (2010)
In addition to the usual advantage of an ice calorimeter of being able to measure slow heat changes, the instrument described here is extremely simple to construct and operate. Specific heat of aluminum, copper, lead and tin metals were determined using the ice calorimeter made with easily accessible materials. The values obtained from specific heat are near to those found in the literature and were 0.204; 0.030; 0.086; 0.046 cal/g °C with an error of theoretical values of 6.84; 1,64; 5.49 and 8.00% for aluminum, copper, lead and tin, respectively.